Semut Honeypot dalam Karya Seni Grafis Stencil Print - Nia Andriani; Yofita Sandra (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This final work is inspired by the social changes that occur in society, especially in cities and villages, which are influenced by technological advances, social media, and tourism. The author raises the theme of the social gap between urban communities that are increasingly individualistic and village communities that still hold fast to solidarity. The visual inspiration comes from the behavior of Honeypot ants, which have a social structure and high cooperation ability in the colony. Through the stencil print graphic art technique, this work expresses the similarity of ant characters with human social phenomena, conveying the values of hard work, mutual cooperation, and solidarity. This work is expected to raise awareness about the importance of togetherness and mutual care in society, as well as a contribution to the study of graphic arts.